Impact of mitral geometry and global afterload on improvement of mitral regurgitation after trans-catheter aortic valve implantation. Issue 3 (September 2016) - Tayyareci, Y; Dworakowski, R; Kogoj, P; Reiken, J; Kenny, C; MacCarthy, P; Wendler, O; Monaghan, M J
Abstract : Objective: To assess the impact of mitral geometry, left ventricular (LV) remodelling and global LV afterload on mitral regurgitation (MR) after trans-catheter aortic valve implantation (TAVI). Methods: In this study, 60 patients who underwent TAVI were evaluated by 3D echocardiography at baseline, 1 month and 6 months after procedure. The proportional change in MR following TAVI was determined by examining the percentage change in vena contracta (VC) at 6 months. Patients having a significant reduction of at least 30% in VC were defined as good responders (GR) and the remaining patients were defined as poor responders (PR). Results: After 6 months of TAVI, 27 (45%) patients were GR and 33 (55%) were PR. There was a significant decrease in 3DE-derived mitral annular diameter and area ( P  = 0.001), mitral valve tenting area (TA) ( P  = 0.05), and mitral papillary muscle dyssynchrony index (DSI) ( P  = 0.05) in the GR group. 3DE-derived LVESV ( P  = 0.016), LV mass ( P  = 0.001) and LV DSI, ( P  = 0.001) were also improved 6 months after TAVI. In addition, valvulo-arterial impedance (ZVA) was significantly higher at baseline in patients with PR ( P  = 0.028). 3DE-derived mitral annular area (β: 0.47, P  = 0.04), mitral papillary DSI (β: −0.65, P  = 0.012) and ZVA (β: 0.45, P  = 0.028) were the strongest independent parameters that could predict the reduction of functional MR after TAVI. Conclusion: GR patients demonstrate more regression in mitral annulus area and diameter after significant decrease in high LVEDP and trans-aortic gradients with TAVI. PR patients appear to have increased baseline ZVA, mitral valve tenting and restriction in mitral valve coaptation. These factors are important for predicting the impact of TAVI on pre-existing MR.